Kedudukan Mahkamah Konstitusi dalam Mekanisme Hubungan antar Lembaga Negara - Arifien, Bustanul; Maulana, Hedwig A.; Candra, Mardi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The Constitutional Court was established following the reform era as part of the judiciary, playing a significant role in strengthening the constitutional system of Indonesia. Pursuant to Article 24C paragraph (1) of the 1945 Constitution of the Republic of Indonesia, the Constitutional Court is vested with the authority to conduct judicial review of statutes to ensure their conformity with the Constitution. As the *guardian of the Constitution*, the Court is responsible for ensuring that all laws and state policies remain consistent with the fundamental principles of the 1945 Constitution and for maintaining the balance of power through the system of *checks and balances*. The theoretical framework used in this research is the theory of the rule of law and the theory of separation of powers. The type of research employed by the author is normative juridical research. The author adopts three approaches, namely the comparative approach, the statutory approach, and the conceptual approach. Legal sources collected consist of primary legal materials, secondary legal materials, and tertiary legal materials, all obtained through literature study and analyzed using a deductive-analytical approach. The research findings indicate that the Constitutional Court's position within the Indonesian constitutional system after the amendment of the 1945 Constitution holds a strategic role in maintaining the balance of power among state institutions, particularly through its authority to resolve constitutional authority disputes. Prior to the amendments, there was no legitimate judicial mechanism available to settle conflicts between state institutions, which often led to institutional tension. The establishment of the Constitutional Court filled this legal vacuum and reinforced the principle of constitutional supremacy, although its authority remains limited by Article 24C paragraph (1) of the 1945 Constitution, which does not yet encompass independent state institutions established by statutory law. In response to the challenges of modern constitutional practice, various proposals have emerged suggesting that the Constitutional Court should be granted broader and more explicit authority, either through interpretation of the Law on Judicial Power or through a limited constitutional amendment. Overall, the Constitutional Court represents a significant corrective measure to the past dominance of executive power and serves as a fundamental pillar in upholding democracy, the rule of law, and a sound and functional system of checks and balances.